Peran KPK dalam Menangani Kasus Korupsi di Indonesia - Rahmanul Rahmanul; Adianto Adianto (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2020)
The role of corruption is a very significant focus in a country based on law, even a measure of the success of a government. One very important element of law enforcement in a country is the war on corruption, because corruption is a cancer that is immune, widespread, permanent and damages all aspects of life as a nation and state including the economy and spatial planning. This research uses a qualitative method with a descriptive approach. The results of this study are the discovery of several cases that were successfully handled by the KPK and this is the result of a good representation of the tasks and functions carried out by the agency..